Heralded amplification of path entangled quantum states. (31st May 2017) - Monteiro, F; Verbanis, E; Vivoli, V Caprara; Martin, A; Gisin, N; Zbinden, H; Thew, R T
Abstract: Device-independent quantum key distribution (DI-QKD) represents one of the most fascinating challenges in quantum communication, exploiting concepts of fundamental physics, namely Bell tests of nonlocality, to ensure the security of a communication link. This requires the loophole-free violation of a Bell inequality, which is intrinsically difficult due to losses in fibre optic transmission channels. Heralded photon amplification (HPA) is a teleportation-based protocol that has been proposed as a means to overcome transmission loss for DI-QKD. Here we demonstrate HPA for path entangled states and characterise the entanglement before and after loss by exploiting a recently developed displacement-based detection scheme. We demonstrate that by exploiting HPA we are able to reliably maintain high fidelity entangled states over loss-equivalent distances of more than 50 km.